Investigating the optimum fineness of the coal grain in the Brown Coal Mine Kakanj in order to fully exploit its calorific value - Avdić, Nurudin; Šehagić, Indira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
In an array of mechanical operations undertaken during the processing of raw coal at the reloading system of the “Vrtlište” open-cut mining in the brown coal mine Kakanj, the tendency is to separate the combustible from the non-combustible parts of coal all with the aim of obtaining a product with higher calorific value and fewer ash components. Depending on the physical and chemical composition of the raw material and the purpose of the obtained product, our objective was to determine the optimal size of the coal grain in the “Brown Coal Mine Kakanj” whereby the most agreeable aspect in terms of the energy value was to separate the valuable fractions from the tailings. It was established that the top-quality granulation in the raw material being delivered to the client in terms of its energy characteristics is -40+35 mm with a calorific value of 16918 kJ/kg followed by -35+20 and -20 +10 with a calorific value of 13035 kJ/kg and 13819 kJ/kg respectively. They generate the smallest amounts of ash after combustion while the free, hygro and total moisture have the lowest values in these samples.